Improvement and validation of a computational model of flow in the swirling well cell culture model. Issue 1 (19th October 2021) - Arshad, Mehwish; Rowland, Ethan M.; Riemer, Kai; Sherwin, Spencer J.; Weinberg, Peter D.
Abstract: Effects of fluid dynamics on cells are often studied by growing the cells on the base of cylindrical wells or dishes that are swirled on the horizontal platform of an orbital shaker. The swirling culture medium applies a shear stress to the cells that varies in magnitude and directionality from the center to the edge of the vessel. Computational fluid dynamics methods are used to simulate the flow and hence calculate shear stresses at the base of the well. The shear characteristics at each radial location are then compared with cell behavior at the same position. Previous simulations have generally ignored effects of surface tension and wetting, and results have only occasionally been experimentally validated. We investigated whether such idealized simulations are sufficiently accurate, examining a commonly‐used swirling well configuration. The breaking wave predicted by earlier simulations was not seen, and the edge‐to‐center difference in shear magnitude (but not directionality) almost disappeared, when surface tension and wetting were included. Optical measurements of fluid height and velocity agreed well only with the computational model that incorporated surface tension and wetting. These results demonstrate the importance of including accurate fluid properties in computational models of the swirling well method. Abstract : Wave breaking is seen in a conventional Computational Fluid Dynamics simulation of liquid in a swirling well (CFD‐ST), but not if surface tension and wetting are included (CFD+ST). This gives a different prediction of the pattern of shear stress experienced by cells cultured on the base of the well.